Antibiotic therapy in acute pancreatitis From global overuse to evidence based recommendations - Párniczky Andrea (PANCREATOLOGY, 2019)
Background & objectives: Unwarranted administration of antibiotics in acute pancreatitis presents a global challenge. The clinical reasoning behind the misuse is poorly understood. Our aim was to investigate current clinical practices and develop recommendations that guide clinicians in prescribing antibiotic treatment in acute pancreatitis. Methods Four methods were used. 1) Systematic data collection was performed to summarize current evidence; 2) a retrospective questionnaire was developed to understand the current global clinical practice; 3) five years of prospectively collected data were analysed to identify the clinical parameters used by medical teams in the decision making process, and finally; 4) the UpToDate Grading of Recommendations, Assessment, Development and Evaluation (GRADE) system was applied to provide evidence based recommendations for healthcare professionals. Results The systematic literature search revealed no consensus on the start of AB therapy in patients with no bacterial culture test. Retrospective data collection on 9728 patients from 22 countries indicated a wide range (31–82%) of antibiotic use frequency in AP. Analysis of 56 variables from 962 patients showed that clinicians initiate antibiotic therapy based on increased WBC and/or elevated CRP, lipase and amylase levels. The above mentioned four laboratory parameters showed no association with infection in the early phase of acute pancreatitis. Instead, procalcitonin levels proved to be a better biomarker of early infection. Patients with suspected infection because of fever had no benefit from antibiotic therapy. Conclusions The authors formulated four consensus statements to urge reduction of unjustified antibiotic treatment in acute pancreatitis and to use procalcitonin rather than WBC or CRP as biomarkers to guide decision-making.